Queer gender identities and videogames - Mark Maletska (Eludamos)
This narrative literature review discusses peer-reviewed research articles connecting queer gender identities and videogames. Its main purpose is to describe directions of research on connections between queer gender identities and videogames, and to indicate gaps and missing connections in existing studies. The analysed material was collected in April–August 2023 using Google Scholar, Web of Science, and Scopus databases. Three major thematic categories were identified in the publications: representation of queer gender identities in videogames; player–avatar connections and gender dysphoria; and queer gender identities in game-related spaces. The main finding of the review is that articles focused on queer people do not tend to address the inherent queerness of videogames. Queer temporality and spatiality are not sufficiently studied in interaction with queer players, and narrative and/or visual elements remain in focus, even when potentially interactive activities like avatar creation are being researched.